Amphibian newts as experimental models for studying weight gain after castration - Mai Takehara; Mitsuki Kyakuno; Kazuko Okamoto; Ichiro Tazawa; Nobuaki Furuno; Megumi Furumitsu; Kazuyoshi Ukena; Takuya Imamura; Takashi Takeuchi; Toshinori Hayashi (Endocrine Journal)
Vertebrate animals often exhibit sexual dimorphism in body shape. In mammals, decreases in sex hormones caused by testicular castration can affect body shape and occasionally lead to pathologies such as obesity. Post-castration obesity can also be problematic for the health of companion animals, including non-mammals. In order to understand the mechanism of post-castration obesity in vertebrates other than mammals, experimental models are required. We examined whether the Iberian ribbed newt, which has recently become a popular experimental model for amphibian research, could serve as a model for analyzing changes in body shape after castration. In newts, new testes can be regenerated after removal of differentiated testes. We analyzed changes in body shape by removing the testes under conditions in which they could regenerate or conditions in which they could not regenerate. Removal of the testes reduced blood testosterone levels. The body weight and abdominal girth of the newts were increased compared with normal male newts. Transcriptome analysis of the liver showed that a set of genes related to lipid metabolism was continuously up-regulated in castrated newts. Our study suggests that changes in body shape after castration are common in vertebrates. Iberian ribbed newts are thus a suitable model for comparative studies of the long-term physiologic- and endocrine-level effects of castration.